THE SEMIOTICS OF BATIK GONGGONG THEME - Miftah amalia hasibuan; Erwin Ashari; Nailul Himmi Hasibuan (English Education Department at FKIP Nommensen University, 2023)
The rapid development of the times can lead to a lack of understanding of culture. A lack of understanding of a culture can lead to a lack of understanding of the message conveyed by a work of art. One of the cultures in Indonesia is batik. Batik is the result of a touch of art and technology. Likewise, the Riau Islands have batik, that is Gonggong batik. Therefore, this study has the objective of knowing the signifier, signified, denotative and connotative meanings of the five Gonggong (Strombus Canurium) batik themes created by Mr Yuspiq. In this study using qualitative descriptive research methods with Roland Barthes semiology analisis approach. The results of this study indicate that the denotative meaning of Gonggong is an icon of the Riau Islands. The connotative meaning is to describe Malay community leaders as having courage, religion, social spirit, harmony, sincerity, and humility in facing life